Differentiating Subchondral Insufficiency Fracture from Osteonecrosis May Help Avoid Unnecessary Total Hip Arthroplasty - Gianakos, Arianna L.; Moya-Angeler, Joaquin; Haring, R Sterling; Li, Angela; Greditzer IV, Harry G.; Lane, Joseph M. (The Journal of Hip Surgery, 2018)
Differentiation of subchondral insufficiency fracture (SIF) from osteonecrosis (ON) is clinically important. The purpose of this study is to correlate the X-ray and magnetic resonance imaging (MRI) findings in cases that have been diagnosed histopathologically as SIF or ON, define features on X-ray and MRI analysis, and identify clinical features that may aid in the diagnosis of SIF from ON. Two blinded radiologists evaluated 104 femoral heads that were diagnosed on histopathology as either ON or SIF. Radiographs and MRIs were evaluated for pertinent radiologic features. If a low signal intensity band was present on MRI, size/depth, shape (parallel/concave/serpentine), and consistency (fatty/edematous/fibrous/mixed) were characterized. About 48.1% of SIF cases were misdiagnosed on X-ray. On MRI, SIF was associated with the presence of a parallel band (p < 0.001), while ON was associated with a serpentine band (p < 0.001). Fifty-eight percent of SIF cases had low intensity signal bands that were fibrous (p < 0.001), while 86% of ON cases had mixed signal bands (p < 0.001). Mean depth for SIF and ON patients was 1.56 mm and 15.36 mm, respectively. Women with bone mineral density <  − 1, and age > 50 years had higher odds of SIF (p = 0.047, p = 0.014, p = 0.034, respectively). SIF is often misdiagnosed on X-ray, and the presence, shape, quality, and depth of the band on MRI can help distinguish SIF from ON. Patients with inconclusive X-ray findings with clinical features that match potential SIF should be considered for MRI. It is reasonable to allow for nonoperative management before recommending operative procedures in patients suspected of having SIF, as these fractures may be possibly managed conservatively.
Keywords: subchondral insufficiency fracture; SIF; osteonecrosis; ON; MRI